Hordein polypeptide patterns in relation to malting quality in Brazilian barley varieties - Echart-Almeida, Cinara; Cavalli-Molina, Suzana (Pesquisa Agropecuaria Brasileira, 2001)
Since there is evidence that malting quality is related to the storage protein (hordein) fraction, in the present work the hordein polypeptide patterns from 13 barley (Hordeum vulgare L.) varieties of different malting quality were analysed in order to explore the feasibility of using hordein electrophoresis to assist in the selection of malting barleys. The formation of clusters separating the varieties with higher malting quality from the others with lower quality suggests that there is a relationship between the general hordein polypeptide pattern and malting quality in the varieties analysed. By the Sperman's correlation test three hordein bands correlated negatively with malting quality in the germplasm studied.